The Workingman's Paradise: An Australian Labour Novel - Miller, John, 1861-1917 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Workingman's Paradise: An Australian Labour Novel" by John Miller is a novel written in the late 19th century. The story is set against the backdrop of Sydney during the late 1880s and early 1890s, focusing on the struggles of the working class, particularly through the eyes of the main characters, Ned and Nellie. Through their interactions and experiences, the book addresses themes of unionism, socialism, and the harsh realities faced by labourers living in impoverished conditions. At the start of the novel, we meet Nellie as she waits for her childhood friend, Ned, who arrives from the Queensland bush. The opening chapters depict conversations between Nellie and her companions that reveal the grim realities of their lives, including unemployment, poverty, and the impact of unionism. The narrative sets up a stark contrast between the idyllic memories of their childhood and the harshness of city life, as revealed through Nellie's observations about her surroundings and her determination to teach Ned about the struggles of their community. As they reconnect, their dialogue hints at larger social issues, including the challenges faced by workers and the inequities in society, laying the groundwork for a narrative steeped in class conflict and personal ambition. (This is an automatically generated summary.)
Release date is 2005-07-27
Produced by Col Choat
Keywords: Working class -- Fiction; Australia -- Fiction